2023
DOI: 10.1186/s12872-023-03098-x
|View full text |Cite
|
Sign up to set email alerts
|

Admission D-dimer to lymphocyte counts ratio as a novel biomarker for predicting the in-hospital mortality in patients with acute aortic dissection

Abstract: Background Inflammatory factors are well-established indicators for vascular disease, but the D-dimer to lymphocyte count ratio (DLR) is not measured in routine clinical care. Screening of DLR in individuals may identify individuals at in-hopital mortality of acute aortic dissection (AD). Methods A retrospective analysis of clinical data from 2013 to 2020 was conducted to identify which factors were related to in-hospital mortality risk of AD. Base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…Our study reinforces these findings by demonstrating that an increase in white blood cell count is an independent risk factor for death. Similarly, elevated D-dimer levels have been previously associated with in-hospital major adverse events, and our results align with those of previous investigations [ 25 – 27 ]. We also identified direct bilirubin level and serum phosphorus level as predictor variables in our model, which have received limited attention in prior studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study reinforces these findings by demonstrating that an increase in white blood cell count is an independent risk factor for death. Similarly, elevated D-dimer levels have been previously associated with in-hospital major adverse events, and our results align with those of previous investigations [ 25 – 27 ]. We also identified direct bilirubin level and serum phosphorus level as predictor variables in our model, which have received limited attention in prior studies.…”
Section: Discussionsupporting
confidence: 93%
“…These findings suggest potential directions for future research. Unfortunately, we did not include calculated inflammatory indicators such as NLR, MLR, PLR, SII, D dimer/l, and SCI in our model [ 27 29 ]. Although these indicators showed differences in univariate logistic and Cox analyses, they were all excluded in the multivariate analyses, contradicting previous research results.…”
Section: Discussionmentioning
confidence: 99%
“…Our study reinforces these ndings by demonstrating that an increase in white blood cell count is an independent risk factor for death. Similarly, elevated D-dimer levels have been previously associated with in-hospital major adverse events, and our results align with those of previous investigations [25][26][27]. We also identi ed direct bilirubin level and serum phosphorus level as predictor variables in our model, which have received limited attention in prior studies.…”
Section: Discussionsupporting
confidence: 89%
“…These ndings suggest potential directions for future research. Unfortunately, we did not include calculated in ammatory indicators such as NLR, MLR, PLR, SII, D dimer/l, and SCI in our model [27][28][29]. Although these indicators showed differences in univariate logistic and Cox analyses, they were all excluded in the multivariate analyses, contradicting previous research results.…”
Section: Discussionmentioning
confidence: 93%
“… 6 Previous study suggested that D dimer was a potential index for AD, with excellent sensitivity but poor specificity diagnostic performance. 15 Furthermore, since the initiation of TBAD is always followed by a cascade of sterile inflammatory response, several inflammation markers have been studied for the diagnosis of AD. 16 , 17 Among these known biomarkers, NLR may be a potent surrogate for the determination of TBAD as reported by other study and our findings.…”
Section: Discussionmentioning
confidence: 99%